Peningkatan Minat Baca Siswa Melalui Pengadaan Taman Baca Siswa - Kurniawati, Vira; Purwanto, Purwanto; Puspitasari, Dakusta; Maryono, Maryono (Universitas Galuh, 2024)
MTS Ma'arif Walisongo 2 Sukomakmur is one of the educational institutions that is required to produce quality students who have superior achievements, both in academic and non-academic fields. One of the efforts to achieve this goal is to implement a culture of literacy for female students. The problem faced by the institution is the need for supporting facilities to carry out literacy activities for female students. The purpose of this service is to provide reading garden facilities with the aim of increasing students' reading interest at MTS Ma'arif Walisongo 2 Sukomakmur. The approach used in this service is PAR (Participation Action Research). The method used is a participatory method, and a reading garden is provided at MTS Ma'arif Walisongo 2 Sukomakmur. Students of MTS Ma'arif Walisongo 2 Sukomakmur were chosen as the main target. In the dedication carried out, the results were able to provide reading garden facilities at MTS Ma'arif Walisongo 2 Sukomakmur with the hope of being able to improve the literacy of MTS Ma'arif Walisongo 2 Sukomakmur students and books in the reading garden can be used as a source of student learning.